2014
DOI: 10.1210/en.2014-1387
|View full text |Cite
|
Sign up to set email alerts
|

Cnr2 Deficiency Confers Resistance to Inflammation-Induced Preterm Birth in Mice

Abstract: Infection-induced inflammation, frequently associated with increased production of proinflammatory cytokines, is considered a significant contributor to preterm birth. A G protein-coupled cannabinoid receptor 2 (CB2), encoded by Cnr2, is expressed in various immune cells and was shown to modulate immune responses. We show here that Cnr2, but not Cnr1, deficient mice are resistant to lipopolysaccharide (LPS)-driven preterm birth and suppression of serum progesterone levels. After LPS challenge, Cnr2 Ϫ/Ϫ mice ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 61 publications
1
20
0
Order By: Relevance
“…As well as cytokines, immune regulators that attenuate TLR-mediated inflammation can impact susceptibility to LPS-induced preterm birth. For example, the cannabinoid receptor Cnr2 modulates dendritic cell production of IL10 and IL6, such that mice genetically deficient in Cnr2 are resistant to LPS-induced preterm birth55. Prostaglandins synthesized after Ptgs2 induction by LPS administration contribute to cervical ripening and other endpoints of parturition, and suppression of Ptgs2 with specific inhibitors can modulate LPS-induced PTD rate56.…”
Section: Discussionmentioning
confidence: 99%
“…As well as cytokines, immune regulators that attenuate TLR-mediated inflammation can impact susceptibility to LPS-induced preterm birth. For example, the cannabinoid receptor Cnr2 modulates dendritic cell production of IL10 and IL6, such that mice genetically deficient in Cnr2 are resistant to LPS-induced preterm birth55. Prostaglandins synthesized after Ptgs2 induction by LPS administration contribute to cervical ripening and other endpoints of parturition, and suppression of Ptgs2 with specific inhibitors can modulate LPS-induced PTD rate56.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 A recent study provided a supporting evidence for the role of IL-10 in preventing preterm birth as increased IL-10 production occurring via augmented cAMP accumulation contributes to resistance to LPS-induced preterm birth in mice with deficiency in G-protein coupled receptor CB2. 109 …”
Section: Il-10 Dysregulation In Adverse Pregnancy Outcomesmentioning
confidence: 99%
“…It is well known that CB2 receptors are expressed in immune, hematopoietic and in almost all peripheral blood immune cells (Pacher & Mechoulam 2011), and its expression can be influenced by various inflammatory agents, e.g., LPS (Carlisle et al 2002, Klein et al 2003. Sun et al (2014) observed that CB2-KO mice had higher serum levels of IL-10 and lower levels of pro-inflammatory cytokines in response to LPS challenge compared with WT controls.…”
Section: Discussionmentioning
confidence: 94%
“…Lazzarin et al (2004) have shown that changes in progesterone levels and FAAH expression are well correlated during the menstrual cycle. The CB2-KO mice are resistant to LPS-driven preterm birth and the endotoxin was unable to decrease maternal progesterone serum levels compared with WT mice (Sun et al 2014), suggesting that ovaries deficient in CB2 are protected from adverse effects of inflammatory insults. In addition, in a model of LPS-induced embryonic resorption, the changes in FAAH activity correlated with changes in progesterone serum levels (Wolfson et al 2013).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation